2020
DOI: 10.3390/su12062428
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Purification Effect of Biochemical Pool Model for Treatment of Pavement Runoff by Aquatic Plants

Abstract: The road runoff after rainfall carries a lot of pollutants that could cause great harm to the water environment. A biochemical pool can be used as a treatment for the road runoff. In order to further improve the efficiency of road runoff treatment by biochemical pool and to evaluate the purification effect of the aquatic plants, two aquatic plants of Iris pseudacorus and Myriophyllum verticillatum were chosen in this research. The effect of different planting densities on the treatment of runoff pollutants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These results came in agreement with many local studies conducted on the Euphrates River and some Iraqi artificial lakes [40]. The reason for the presence of some species and types of algae and not others may be attributed to the density of aquatic plants in the lake, as the presence of these plants helps the growth of multiple and diverse numbers of phytoplankton that stick to them and which separate from them as a result of various reasons, which causes their spread in the water, increasing the number of their types [41], or the effect of pollutants that may affect the biological activities of algae in addition to the concentration of compounds important for the sustainability of their life and can cause high concentrations of heavy elements to enrich one group of algae without the other because they are active in such environments [42]. The results showed a clear dominance of the species Cyclotella ocellata, Achanthes minutissima, Nietzsche palea, and these species have the ability to tolerate a wide range of nutrients and salinity [43][44][45], and this indicates the presence of pollution in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results came in agreement with many local studies conducted on the Euphrates River and some Iraqi artificial lakes [40]. The reason for the presence of some species and types of algae and not others may be attributed to the density of aquatic plants in the lake, as the presence of these plants helps the growth of multiple and diverse numbers of phytoplankton that stick to them and which separate from them as a result of various reasons, which causes their spread in the water, increasing the number of their types [41], or the effect of pollutants that may affect the biological activities of algae in addition to the concentration of compounds important for the sustainability of their life and can cause high concentrations of heavy elements to enrich one group of algae without the other because they are active in such environments [42]. The results showed a clear dominance of the species Cyclotella ocellata, Achanthes minutissima, Nietzsche palea, and these species have the ability to tolerate a wide range of nutrients and salinity [43][44][45], and this indicates the presence of pollution in general.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a clear dominance of the species Cyclotella ocellata, Achanthes minutissima, Nietzsche palea, and these species have the ability to tolerate a wide range of nutrients and salinity [43][44][45], and this indicates the presence of pollution in general. The Iraqi water environment is good for the growth of and the presence and diversity of phytoplankton, which has a low alkalinity and an abundance of nutrients, but recently there is a threat to the water environment, which is drought and lack of rain, which negatively affects aquatic organisms, including phytoplankton [41]. Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of three parts, namely the physical pool, chemical pool, and biochemical pool, which can be used to remove pollutants from varying pavement runoff. Wang et al [21] analyzed the role of aquatic plants in a pavement-runoff-integrated treatment system for the purification of pavement runoff. Their results showed that aquatic plants can effectively remove SS, COD, petroleum, Zn, and Cu.…”
Section: Introductionmentioning
confidence: 99%
“…During expressway construction and operation, many pollutants, such as solids, nutrients and heavy metals will be produced [ 1 ] and the surface runoff will have a negative impact on the water environment [ 2 ]. Also, most expressways are linear, and crossing some important rivers, tourist sites, and water conservation areas is inevitable.…”
Section: Introductionmentioning
confidence: 99%